2013
DOI: 10.1530/eje-13-0087
|View full text |Cite
|
Sign up to set email alerts
|

Associations of TSH levels within the reference range with future blood pressure and lipid concentrations: 11-year follow-up of the HUNT study

Abstract: Objective: In cross-sectional studies, TSH levels within the reference range have been positively associated with blood pressure and adverse serum lipid levels. In a prospective study, we aimed to determine whether differences in TSH levels within the reference range are associated with future levels of blood pressure and lipids. Design: We conducted a prospective population-based study. Methods: In 9709 women and 4644 men without previous thyroid disease who had a baseline TSH level of 0.45-4.5 mU/l, we studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
47
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 25 publications
9
47
1
Order By: Relevance
“…Across studies, the prevalence of SCH (like overt hypothyroidism) is consistently higher in women than in men (Table 2) (17)(18)(19)(20)(21)23,25,27,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In the Whickham study, the prevalence of SCH in women was 7.5%, nearly three times the prevalence in men (2.8%) (19).…”
Section: Sexmentioning
confidence: 97%
See 1 more Smart Citation
“…Across studies, the prevalence of SCH (like overt hypothyroidism) is consistently higher in women than in men (Table 2) (17)(18)(19)(20)(21)23,25,27,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In the Whickham study, the prevalence of SCH in women was 7.5%, nearly three times the prevalence in men (2.8%) (19).…”
Section: Sexmentioning
confidence: 97%
“…In a recent study, Asvold and colleagues reported that the prevalence of untreated SCH in Norway decreased over an 11-year period from 1995 to 1997 (HUNT 2 study) to 2006-2008 (HUNT 3 study) (25). In HUNT 2 and HUNT 3, SCH was defined as TSH > 4.5 mIU/l combined with normal levels of FT4.…”
Section: Historical Prevalence Of Schmentioning
confidence: 99%
“…Iqbal et al in a study of a population of 5 872 euthyroid patients in the Tromso study, found a positive association between TSH and systolic and diastolic blood pressure; they reported that only diastolic hypertensive patients have higher serum TSH levels. In an 11 year follow-up study of 14 353 individuals with serum TSH levels within reference range higher TSH levels at the baseline were associated with elevated levels of blood pressure at follow-up, but the strength of the associations suggested that the findings may not be clinically relevant [25].…”
mentioning
confidence: 97%
“…Moreover, to date, a series of contradictory relationships have been noted. Indeed, a linear relationship between serum TSH levels and BP (both systolic and diastolic) was observed by Asvold, et al [5,6]. However, no such associations were observed in two further stud-…”
mentioning
confidence: 86%